Pendampingan POKDAKAN Krido Yuwono Minapadi Technopark Panembangan dalam Optimalisasi Manajemen Kualitas Air Perikanan untuk Peningkatan Ketahanan Pangan Kabupaten Banyumas - Fikriyya, Nabela; Sujadi, Frentina Murti; Putri, Adinda Kurnia; Anjaini, Jefri; Raharja, Ferry Cahya; Karimah, Fatiya (Universitas Mataram, 2025)
Regional food security is largely determined by the sustainability of fisheries production, one of which is through the minapadi system that integrates fish and rice cultivation. The main obstacle that often arises is suboptimal water quality management, which reduces fish productivity and aquatic ecosystem health. This community service activity aims to enhance the capacity of the Krido Yuwono Minapadi Technopark Panembangan Fish Farmers Group (POKDAKAN) in fisheries water quality management to support food security in Banyumas Regency. The assistance method was carried out participatively through socialisation and training on water quality management theory, field practice in measuring physical-chemical parameters (pH, dissolved oxygen and temperature), installation of simple monitoring devices, and evaluation of competency improvement through pre-tests and post-tests. The results of the activity showed an average increase in participants' knowledge from 47% to 76%, the implementation of a routine water quality monitoring schedule, and improvements in key parameters, including pH stability and real-time knowledge of water quality conditions. These findings confirm that participation-based assistance is effective in improving the technical skills of farmers, maintaining the quality of aquaculture water, and supporting the sustainability of the minapadi system as a strategy for strengthening regional food security.